PEMBUATAN VIDEO ANIMASI “GREEN TOURISM” SEBAGAI MEDIA EDUKASI DALAM UPAYA MENGURANGI PERMASALAHAN SAMPAH PLASTIK - Ramadhan, Ethan Zahrul; Ramadhani, Nurul Fathya Rahma Puspita; Jamilulhaqq, Zakky Nooruddin (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2022)
Places like Bali, Tower of Pisa, The Eiffel Tower and such are called Tourist Attractions. The reason is that because of the functionality of the system is to serves as a recreational for tourists and best spots during vacations. However plastic waste and litterings have been a major ongoing issue across the world, not only it’s ruining the environment but it also reduces the lifespan of the surrounding ecosystem of the tourist attraction themselves. Indonesia has been the world’s number 3 worst plastic processing country in the world and the places that usually a go to spot for tourists have been contaminated by plastics, either by the locals or the tourists that currently visiting the place. According to Nat Geo’s report that in 2050, there will be at least 12 trillion plastic waste if the accumulation of plastic wastes is not prevented. Educating people to increase and spread awareness about how bad the plastic waste problem are now and how we as an individual reduces the upcoming plastic waste disaster is important, therefore an animation video that acts as an awareness media is created in hope to delivers the messages and prevent people from littering on a tourist attractions.